Association of obesity with illness severity in hospitalized patients with COVID-19: A retrospective cohort study. Issue 2 (March 2021) - Suresh, Suraj; Siddiqui, Mohammad; Abu Ghanimeh, Mouhanna; Jou, Jessica; Simmer, Stephen; Mendiratta, Vivek; Russell, Sarah; Al-Shammari, Mustafa; Chatfield, Abigail; Alsheik, Eva; Dang, Duyen; Genaw, Jeffrey; et al.
Highlights: Obese patients hospitalized with COVID-19 are younger and more likely to be female and African American compared to patients without obesity. Obesity in patients with COVID-19 is independently associated with higher rates of ICU admission and intubation. Obesity is not associated with increased mortality or higher readmission rates in hospitalized COVID-19 patients. Abstract: Background: Although recent studies have shown an association between obesity and adverse coronavirus disease 2019 (COVID-19) patient outcomes, there is a paucity in large studies focusing on hospitalized patients. We aimed to analyze outcomes associated with obesity in a large cohort of hospitalized COVID-19 patients. Methods: We performed a retrospective study at a tertiary care health system of adult patients with COVID-19 who were admitted between March 1 and April 30, 2020. Patients were stratified by body mass index (BMI) into obese (BMI ≥ 30 kg/m 2) and non-obese (BMI < 30 kg/m 2) cohorts. Primary outcomes were mortality, intensive care unit (ICU) admission, intubation, and 30-day readmission. Results: A total of 1983 patients were included of whom 1031 (51.9%) had obesity and 952 (48.9%) did not have obesity. Patients with obesity were younger (P < 0.001), more likely to be female (P < 0.001) and African American (P < 0.001) compared to patients without obesity. Multivariable logistic models adjusting for differences in age, sex, race, medical comorbidities, and treatment modalities revealed no difference in 60-day mortality and 30-day readmission between obese and non-obese groups. In these models, patients with obesity had increased odds of ICU admission (adjusted OR, 1.37; 95% CI, 1.07−1.76; P = 0.012) and intubation (adjusted OR, 1.37; 95% CI, 1.04−1.80; P = 0.026). Conclusions: Obesity in patients with COVID-19 is independently associated with increased risk for ICU admission and intubation. Recognizing that obesity impacts morbidity in this manner is crucial for appropriate management of COVID-19 patients.